2019
DOI: 10.3390/f10121049
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expressions of Visitors in Forests along the Urbanization Gradient: What Can We Learn from Selfies on Social Networking Services?

Abstract: People’s satisfaction towards the experience in forests is one of most important feedbacks that forest park managers need to meet positive visitors’ experiences. Although the drawbacks of questionnaire methodology are obvious for data collection from self-reported scores at the landscape scale, few alternative methods have been proposed. In this study, nine urban forest parks along the urbanization gradients in three capital cities of Northeast China were targeted to investigate their visitors’ selfies from so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 51 publications
5
49
2
Order By: Relevance
“…The Sina Micro-Blog (SMB; Sina Inc., Beijing, China) was chosen as the platform of SNS to collect facial photos using the method of Wei et al [19]. SMB is widely used by Chinese web-users and functions similar to Twitter (NYSE: TWTR, San Francisco, CA, USA) that supplies a platform to pose real-time mini-blogs to the internet with comments and images (photos).…”
Section: Photo Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sina Micro-Blog (SMB; Sina Inc., Beijing, China) was chosen as the platform of SNS to collect facial photos using the method of Wei et al [19]. SMB is widely used by Chinese web-users and functions similar to Twitter (NYSE: TWTR, San Francisco, CA, USA) that supplies a platform to pose real-time mini-blogs to the internet with comments and images (photos).…”
Section: Photo Collectionmentioning
confidence: 99%
“…Traditionally, questionnaires provided a common method to evaluate people perception. Evaluation through self-reported scores has several apparent biases from subjective emotion of respondents, real-time mood, problematic questions, and social-role restricted results [19]. Facial expression represents an emotional response to a stimulus and/or a communicative behavior in a social situation, which can be termed as Duchenne (a felt expression with an emotion cue) and non-Duchenne ways (an unfelt expression with a communicative cue), respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…The first evidence comes from two recent studies from China. In one study, selfies uploaded in social media were related to the location at which the picture was taken [ 50 ]. This study indicated that software-measured facial expressions, especially from women, vary with the distance to the city center.…”
Section: Discussionmentioning
confidence: 99%
“…The perception to infrastructure and openness are determinants of the emotional variation at different places [17,18]. When urban forests at different places were focused, people will also show spatial variation of emotional expressions that resulted from the perception to environmental factors [19,20]. Again, the validation of the instrument for facial expression recognition is lacking to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…FireFACE ver. 3.0 has been used to detect the combined effects of geographical variation across urbanization gradient on facial expressions of urban forests in Northeast China [19]. Therefore, FireFACE has the desired precision in facial analysis for people in urban forests although mostly they tended to show subtle expressions.…”
Section: Introductionmentioning
confidence: 99%